UPAYA MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL MELALUI PERMAINAN TRADISIONAL BAKIAK UNTUK ANAK KELOMPOK B1 PAUD PELITA KASIH - pudensia ratnasari; Elizabeth Prima; Christiani Endah Poerwati (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
Early Childhood socio-emotional abilities are important to be developed and stimulated optimally by making use of learn-through-play activities. One of the stimulations applied is through the traditional game of clogs (in Bahasa: bakiak). This study aims to determine the improvement of social-emotional skills through traditional games of clogs for children in Group B1 PAUD Pelita Kasih. The research subjects were 18 children of Group B1 PAUD Pelita Kasih. This research was carried out in 2 cycles, namely Cycle I and Cycle II, with each stage, namely planning, implementation, observattion, and reflection. Based on the results of the study, it can be concluded that the traditional game of clogs can improve the social and emotional abilities of the students of Group B1 PAUD Pelita Kasih. This can be seen in the increase in the percentage of completeness that occurred in the initial condition that from 18 students only 4 children (22.22%) achieved completeness, in Cycle 1 it increased to 8 children (44.44%), and in Cycle II it increased again to 15 children. (83.33%). So it can be concluded that the traditional game of clogs can be an alternative stimulation in improving the social-emotional skills of early childhood in Group B1 PAUD Pelita Kasih